Implementasi Sistem Informasi Akuntansi Digital dalam Meningkatkan Efisiensi Proses Transaksi Penjualan di PT Java Energy Semesta - Agustina, Linda; Tituk Diah Widajantie (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2026)
This study aims to analyze the impact of implementing a digital accounting information system (AIS) on the efficiency of the input and validation processes of sales transactions at PT Java Energy Semesta. The method used is descriptive qualitative with data collection techniques through direct observation, informal interviews, and documentation during the five-month MBKM internship program. The analysis technique is carried out by comparing conditions before and after digitalization, specifically in terms of input time, validation, and transaction error rates. The results show that digitalization of the accounting system through the implementation of ERP can reduce transaction input time by 50%, validation time by 62.5%, and error rates by 71.4%. The implication of this study is that digitalization has been proven not only to increase the efficiency and accuracy of transaction processes, but also encourages increased transparency, accountability, and job satisfaction of finance staff. This study provides empirical evidence for other companies wishing to adopt digital systems in accounting and serves as a reference for academics in understanding the real practices of implementing information technology in the modern world of accou.